Radiation Signature in Plasma Metabolome of Total-Body Irradiated Nonhuman Primates and Clinical Patients - Tichy, Ales; Carpenter, Alana D; Li, Yaoxiang; Rydlova, Gabriela; Rehulka, Pavel; Markova, Marketa; Milanova, Marcela; Chmil, Vojtech; Cheema, Amrita K; Singh, Vijay K (International journal of molecular sciences, 2024)
In the last decade, geopolitical instability across the globe has increased the risk of a large-scale radiological event, when radiation biomarkers would be needed for an effective triage of an irradiated population. Ionizing radiation elicits a complex response in the proteome, genome, and metabolome and hence can be leveraged as rapid and sensitive indicators of irradiation-induced damage. We analyzed the plasma of total-body irradiated (TBI) leukemia patients (n = 24) and nonhuman primates (NHPs; n = 10) before and 24 h after irradiation, and we performed a global metabolomic study aiming to provide plasma metabolites as candidate radiation biomarkers for biological dosimetry. Peripheral blood samples were collected according to the appropriate ethical approvals, and metabolites were extracted and analyzed by liquid chromatography mass spectrometry. We identified an array of metabolites significantly altered by irradiation, including bilirubin, cholesterol, and 18-hydroxycorticosterone, which were detected in leukemia patients and NHPs. Pathway analysis showed overlapping perturbations in steroidogenesis, porphyrin metabolism, and steroid hormone biosynthesis and metabolism. Additionally, we observed dysregulation in bile acid biosynthesis and tyrosine metabolism in the TBI patient cohort. This investigation is, to our best knowledge, among the first to provide valuable insights into a comparison between human and NHP irradiation models. The findings from this study could be leveraged for translational biological dosimetry.
Keywords: Female; lidé středního věku; Animals; biologické markery; mužské pohlaví; Humans; dospělí; Macaca mulatta; leukemie; Whole-Body Irradiation; lidé; ionizující záření; Middle Aged; zvířata; celotělové ozáření; ženské pohlaví; metabolomika; Metabolome; Leukemia; Radiation, Ionizing; metabolom; Adult; Biomarkers; Male; Metabolomics